Electrochemical Extraction of Praseodymium by Formation of Zn-Pr Alloy in LiCl-KCl Melts with the Assistance of ZnCl2 and Liquid Zn. Issue 4 (3rd March 2017) - Xue, Yun; Ji, De-Bin; Yan, Yong-De; Zhang, Mi-Lin; Liu, Yu-Hui; Wang, Pu; Yin, Tai-Qi; Li, Peng; Zhao, Yang; Wang, Jun
Abstract : The electrochemical behavior of Zn(II) and Pr(III) in LiCl-KCl melts was investigated by different electrochemical measurements. On W electrode, the reduction of Zn(II) to Zn(0) in LiCl-KCl melts was realized by a single reaction step. In LiCl-KCl-ZnCl2 -PrCl3 melts, cyclic voltammetry, square wave voltammetry and open circuit chronopotentiometry showed that six kinds of Zn-Pr intermetallic compounds could be formed at 923 K. However, when the experimental temperature increased to 948 K, eight potential plateaus corresponding to the formation of eight different kinds of Zn-Pr intermetallic compounds appeared in the open circuit chronopotentiogram. Electrochemical extraction of praseodymium was implemented by the formation of Zn-Pr alloys, which were manufactured by galvanostatic electrolysis on W electrodes in LiCl-KCl-ZnCl2 -PrCl3 melts and by galvanostatic and potentiostatic electrolysis on liquid Zn electrode in LiCl-KCl-PrCl3 melts, respectively. After electrolysis, the alloys were analyzed by XRD and SEM equipped with EDS analysis.